Chemical composition of hydrothermal fluids in the central and southern Mariana Trough backarc basin. (November 2015) - Ishibashi, Jun-ichiro; Tsunogai, Urumu; Toki, Tomohiro; Ebina, Naoya; Gamo, Toshitaka; Sano, Yuji; Masuda, Harue; Chiba, Hitoshi
Abstract: We present a geochemical data set from hydrothermal fluids collected from the central and southern Mariana Trough during dive programs conducted in the 1990s. The fluid samples were collected from two hydrothermal fields: (1) the Alice Springs field (18°13′N, 144°42′E, water depth: 3600 m) on the axial ridge crest of the central Marana Trough; and (2) the Forecast field (13°24′N, 143°55′E, water depth: 1470 m) on Peak B seamount, one of a cluster of small volcanic seamounts which represents a unique tectonic setting in the southern Mariana Trough. Gas geochemistry of the Alice Springs fluid showed He and C isotope ratios in the range of MORB, whereas that of the Forecast fluid showed a higher CO2 / 3 He ratio and 13 C-enriched isotope ratio, both of which are commonly recognized in hydrothermal fluids from intraoceanic arc volcanoes. The major and minor element composition of the Alice Springs fluid is characterized by enrichment in mobile alkali elements such as K, Rb and Cs. This geochemical signature is in accordance with the well-known characteristics of basaltic lava collected from the same area, which show substantial enrichment in incompatible elements. As interpreted in previous petrological studies, this signature is considered to be an arc geochemical signal reflecting contribution from the subduction component. The B concentration of the Alice Springs fluid is also high and is another arc geochemical signal. The Forecast fluid, by contrast, did not show enrichment in the mobile alkali elements, although its B concentration is high. The Forecast fluid is characterized instead by enrichment in Ca and Sr coupled with depletion in Na and Li. As discussed in previous studies, this signature is attributed to hydrothermal reactions at rather low temperature due to the shallow water depth. We recognize two different arc geochemical signals in these two hydrothermal fluids: mobile alkali elements in the Alice Spring fluid and gaseous species in the Forecast fluid. This difference could reflect different behaviors of these species during magmatic processes in the mantle wedge beneath the Mariana Trough backarc spreading center.